(3EceGd JgPjH GdceGd aj CSeGA GdQLGds - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3ef GSeg HGH hHGPGe Hf YejQ GdMfai GdTGei s
(3BNQgG (B:s
(3aPcQ Yf CMeO Hf MfHd Gfg cGf jQhi McGjGJ Yf GdMSf Gfg SeY ef YGFTI hgj Jbhd s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B((3eUWdM (B15) s
Keywords: (3GdJGQjNs